How to measure the governance pillar of agrarian sustainability - BACHEV, Hrabrin Ianouchev (Journal of Economic and Social Thought, 2020)
Abstract. A need to include “the fourth” Governance pillar in the concept for understanding and the assessment system of (overall and) agrarian sustainability is increasingly justified in academic literature and finds place in the frameworks of government, international, private, etc. organizations Nevertheless, still there is no general consensus on: whether and how to include the governance as a new pillar of agrarian sustainability; how to define the governance sustainability; what are the relations between the governance sustainability of a farming enterprise and agriculture; what are the critical factors of governance sustainability; how to formulate, select, measure and integrate diverse sustainability indicators; and how to properly evaluate the level of governance sustainability, etc. In Bulgaria, like in many other countries, practically there are no comprehensive assessments of the governance sustainability of agriculture and its importance for the overall agrarian development. This study tries to fill the gap and suggests a holistic framework for understanding and assessing the governance sustainability of Bulgarian agriculture. The newly elaborated approach is “tested” in a large-scale study for assessing the governance sustainability of country’s agriculture at national, sectoral, regional, eco-system and farm levels.The study has proved that it is important to include the “missing” Governance Pillar in the assessment of the Integral sustainability of agriculture and sustainability of agro-systems of various type. Multiple Principles, Criteria and Indicators assessment of the Governance sustainability of Bulgarian agriculture indicates that the Overall Governance Sustainability is at a “Good” but very close to the “Satisfactory” level. Besides, there is a considerable differentiation in the level of Integral Governance sustainability of different agro-systems in the country. Last but not least important, results on the integral agrarian sustainability assessment based on micro (farm) and macro (statistical, etc.) data show some discrepancies which have to be taken into consideration in the analysis and interpretation, while assessment indicators, methods and data sources further improved. Having in mind the importance of holistic assessments of this kind for improving the agrarian sustainability in general, and the Governance sustainability of agriculture in particular, they are to be expended and their precision and representation increased. The later requires improvement of the precision through enlargement of surveyed farms and stakeholders, and incorporating more “objective” data from surveys, statistics, expertise of professionals in the area, etc. Since the elaboration of an effective framework for Governance sustainability assessment is far from complete our and other emerging suggestions have to be further discussed, experimented, improved and adapted to the specific conditions of evaluating agricultural system and needs of decision-makers at different levels. Keywords. Governance sustainability, Assessment, Agriculture, Agricultural systems, Bulgaria. JEL. Q12, Q13, Q15, Q18.